Extrinsic factors involved in the pigmentation of dental composite resins - Vásquez L., José Mateo (2022)
Dental composite resins were introduced in the first half of the 20th century as a mechanical-aesthetic advance in the field of restorative dentistry, as a response to silicates, which at that time was the first choice restorative material, composite resin contains a matrix of organic made up of Bis-GMA and other dimethacrylate monomers (TEGMA, UDMA, silorans) doing them susceptible to pigmentation with extrinsic substances, in this case drinks, such as red wine, tea and coffee are the main cause of the pigmentation of resins. Objective: To Review and analyze the available literature that answers the question: what are the most common extrinsic factors that cause pigmentation of composite resins?